Research progress of stem cell therapy for ischemic stroke. Issue 3 (28th September 2021) - Li, Ting; Zhu, Gao‐Hong
Abstract : Ischemic stroke is a serious cerebrovascular disease with high morbidity, disability and mortality. There is no doubt that the disease has a severe impact on the physical and mental health and quality of life of patients, as well as impose a heavy burden on families and societies. Unfortunately, there has been a lack of effective treatment. This overview reviews the pathophysiology of stem cell therapy in Ischemic stroke, and discuss its effects on neurogenesis, the latest clinical trials, and advances in tracking and monitoring of endogenous and exogenous stem cells.